Acceptability and feasibility of using digital technology to train community practitioners to deliver a family-based intervention for adolescents with drug use disorders during the COVID-19 pandemic. (December 2021) - Busse, Anja; Kashino, Wataru; Suhartono, Sanita; Narotama, Narendra; Pelupessy, Dicky; Avicenna Fikri, Annafi; Essau, Cecilia A.
Highlights: It is acceptable and feasible to deliver a family-based intervention training (Treatnet Family) via a digital platform. Practitioners who participated in the Treatnet Family training showed an increase in knowledge about family-based intervention. Most practitioners reported that they have confidence in conducting Treatnet Family and in applying the core skills of a family-based intervention. Abstract: Introduction: By adhering to government preventative messages to stay-at-home and social distancing during the COVID-19 pandemic, training practitioners in person in implementing a family-based intervention (i.e., Treatnet Family) is not possible. The present study examined the feasibility and acceptability of using digital technology to remotely deliver Treatnet Family training to practitioners in community counselling services in Indonesia. Method: Fifteen practitioners, from the association of addiction counsellors in Indonesia, participated in the Treatnet Family workshop remotely. The training was delivered by four national Treatnet Family trainers remotely via a digital platform for five days with additional take-home assignments. Results: All practitioners reported that Treatnet Family training have enhanced their skills in working with adolescents and their family. Most practitioners reported having confidence in conducting Treatnet Family and in applying core skills of family-based intervention. Participating in the workshop enabled practitioners to learn the core skills of the Treatnet Family at their own pace. However, some practitioners also stated few disadvantages in remote training, including having limited time for the discussion and feeling overwhelmed with the assignments. Some find it hard to attend such training from their home due to distractions. Conclusion: Digital technology is acceptable and feasible method for training community practitioners to deliver Treatnet Family to adolescents with SUDs and their families in Indonesia. These findings can inform the way to use digital technology to deliver core family-based skills to community practitioners in other low-resource settings.